THE EFFECT OF SCIENTIFIC INQUIRY LEARNING MODEL USING MIND MAPPING AND CRITICAL THINKING ABILITY TOWARD STUDENT’S SCIENCE PROCESS SKILLS IN SENIOR HIGH SCHOOL - Widya Suryani; Mara Bangun Harahap; Karya Sinulingga (Universitas Negeri Medan, 2017)
This study aims to analyze: science process skills taught with scientific inquiry model using mind mapping better than students taught with conventional learning, physics science process skills students who have the ability to think critically using scientific inquiry model above average better than students who have the ability to think critically using conventional models above average, and the interaction of scientific inquiry learning model using mind mapping media with students 'critical thinking ability in improving students' physics science process skills. This research is a quasi experimental research with two group pretest-posttest design design. The research population is all students of grade X SMA Gajah Mada Medan first semester of academic year 2017/2018. The sample in this study was taken by cluster random sampling. The instruments used are tests of science process skills and critical thinking ability tests. The resulting data were analyzed using two-way ANOVA. The result of the research shows that: science process skill of students taught with scientific inquiry model using mind mapping better than students taught by conventional learning, physics science process skill of students who have critical thinking ability using scientific inquiry model above average better than students who have the ability to think critically using conventional models above average, and there is the interaction of scientific inquiry learning model using mind mapping with students 'critical thinking ability in improving students' science process skills.